UPAYA PENINGKATAN PRODUKTIVITAS BERDASARKAN ANALISIS PENGARUH KESELAMATAN, KESEHATAN KERJA, DAN LINGKUNGAN (K3L) TERHADAP PRODUKTIVITAS TENAGA KERJA DI PABRIK GULA PT. KREBET BARU MALANG - Na'ali, Sidi; Wardana, ING; Soenoko, Rudy (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2013)
In industrialization we need to improve productivity and efficiency which it helps to challenge and can produced high performance product. One of factor that influence productivity is about safety, healthy and environment where we work. We could said that because K3L could build competent, professional and skilled worker. This research measure about relationship between safety, healthy, and environment variable with productivity worker. We use Structural Equation Modeling (SEM) to examine data because with SEM, we will get simultaneous causality relationship between variable. With considering variable that influence in productivity, we can give some recommendation to improve productivity. Based on data and result we got some variable that give significant influence, such as: comprehension in vision and mission in K3L, fire extinguisher availability, safety sign utilization, K3L training, machine jig and fixture completeness, machine lay out and tool storage, machine and tool maintenance. Healthy variable that influence productivity is salary, scholarship, disable factor from worker, worker competence, optimizeÂ polyclinic, optimize medical personal, accident assurance. Environment variable that influence productivity isÂ trash bin availability, good lighting, processing waste, good air circulation, safety from danger in work environment, good temperature, bathroom sink availability, and WC avalialbility.